The level and determinants of multimodal travel behavior: Does trip purpose make a difference?. Issue 2 (1st February 2023) - An, Zihao; Heinen, Eva; Watling, David
Abstract: Multimodality refers to the phenomenon of using more than one mode of transport in a given period. Encouraging multimodality potentially provides an effective solution to reduce CO2 emissions and induce modal shifts toward sustainable transport. This research investigates the extent to which the level and correlates of multimodality differ by trip purpose. We used one-week travel diaries of the English National Travel Survey. Our analyses showed that the level of multimodality varied by trip purpose and the associated time-space variability as well as by the number of trip stages. We found that the level of variability in departure time and travel distance was greater for leisure trips than for maintenance trips, which was in turn greater than for work trips. Trips that were more variable in departure time and travel distance showed on average higher levels of individual multimodality, but only if sufficient stages (at least 3) were made. Moreover, we detected cross-purpose disparities in correlates of multimodality in terms of significance and variance explained. This research may provide support to the development of trip purpose-specific policies aiming to increase multimodality.